Effectiveness of Sodium Bicarbonate Infusion on Mortality in Critically Ill Children With Metabolic Acidosis - Wang, Huabin; Liang, Rui; Liang, Tianqi; Chen, Songyao; Zhang, Yulong; Zhang, Lidan; Chen, Chun (Frontiers in Pharmacology, 2022)
Objective: Metabolic acidosis often occurs in the paediatric intensive care unit (PICU). Although sodium bicarbonate (SB) has been widely used in paediatrics, data on the effect of SB on children with metabolic acidosis in the PICU are scarce. Methods: Patients with metabolic acidosis who were treated with SB within 48 hours of PICU admission were screened. Multivariate logistic regression, subgroup analysis, and propensity score matching (PSM) were used to investigate the relationships between SB infusion and clinical outcomes. Results: A total of 1595 patients with metabolic acidosis were enrolled in this study. In the multivariate logistic regression model, SB infusion was not correlated with in-hospital mortality (odds ratio (OR) 0.87, 95% confidence interval (CI) 0.47-1.63, p = 0.668), but was significantly correlated with hypernatraemia (OR 1.98, 95% CI 1.14-3.46, p = 0.016), hypokalaemia (OR 2.01, 95% CI 1.36-2.96, p < 0.001), and hypocalcaemia (OR 4.29, 95% CI 2.92-6.31, p < 0.001). In the pH value, lactate level, acute kidney injury level, age grouping, and anion gap level subgroups, the ORs for SB and in-hospital mortality were not statistically significant. After PSM, the results remained unchanged. Conclusion: SB infusion does not reduce the in-hospital mortality of severely ill children with metabolic acidosis and increases the risk of hypernatraemia, hypokalaemia, and hypocalcaemia. More effort should be focused on eliminating the causes of metabolic acidosis rather than SB infusion.